Effectiveness Of A Multisensory Web-Based Reading Instruction Among Preschoolers: A Pilot Study - Tan, Yen Vee (Universiti Malaysia Sarawak, (UNIMAS), 2023)
This study aimed to determine the effectiveness of multisensory digital technology among preschoolers on alphabet knowledge. Specifically, the effectiveness of this technology was assessed through pre-test and post-test evaluations of children's letter name knowledge and letter recognition skills—recognized as crucial predictors of alphabet knowledge. Pretest-Posttest Waitlist Control Group Design was used in this study, and a total of 18 preschoolers from a public preschool were involved. Participants were divided into experimental and waitlist control groups respectively. Following the initial assessments, the participants were paired based on their existing alphabet knowledge and randomly assigned to either the waitlist control group or the experimental group. The children in the waitlist control group received standard classroom teaching, while those in the experimental group received intervention using the READie system. Data were analyzed using the Mann-Whitney U Test and Wilcoxon Signed Rank Test. The results indicate that, except for a noteworthy improvement in uppercase letter name knowledge among the experimental group, there were no significant differences in the pre-test and post-test scores between both the experimental and control groups. Furthermore, no significant disparities in performance were found between the experimental and control groups. Thus, this study provides partial evidence of the effectiveness of the READie system in helping children to learn uppercase letter names. The implications of these findings for future research and educational practices are discussed.